Permanent magnetic strontium ferrite material as well as preparation method and application thereof
By first mixing rare earth oxides and additives to form a composite additive powder, and then mixing them with strontium ferrite prefix, the problem of the coercive force of permanent magnet strontium ferrite material decreases when increasing residual magnetism, and the overall magnetic performance of the material is improved.
Patent Information
- Application Number
- CN202411894229.4
- Authority / Receiving Office
- CN · China
- Patent Type
- Applications(China)
- Current Assignee / Owner
- Filing Date
- 2024-12-20
- Publication Date
- 2025-03-18
- Estimated Expiration
- 2044-12-20
AI Technical Summary
The prior art is difficult to maintain or increase the coercive force while increasing the residual magnetism of the permanent magnet strontium ferrite material, resulting in limited overall improvement of magnetic properties.
First mix the rare earth oxide and additives to form a uniform composite additive powder, and then mix it with strontium ferrite pre-sintering material to ensure that the composite additives are evenly distributed and synergistically during the sintering process to improve the magnetic properties of the material.
Through this method, the residual magnetic and coercive forces of the permanent magnet strontium ferrite material have been improved, and the M value is within the range of 5383-5415, and the overall magnetic performance is better.
Smart Images

Figure CN119638398A_ABST
Abstract
Description
Technical Field
[0001] The invention relates to the technical field of permanent magnet strontium ferrite preparation, and in particular to a permanent magnet strontium ferrite material and a preparation method and application thereof. Background Art
[0002] Permanent strontium ferrite with a hexagonal magnetoplumbite structure has become a widely used permanent magnetic material due to its excellent stability and high cost performance. With the expansion of application fields and strict requirements on material performance, how to further improve its magnetic properties has become the focus of current research.
[0003] Studies have shown that in addition to changing the intrinsic properties of strontium ferrite by ion substitution, improving the corresponding preparation process can also help improve the density, orientation and existence rate of single-domain particles of strontium ferrite, thereby improving the remanence and coercivity of strontium ferrite. In the way of improving the process, the use of additives is an effective method. Different additives can play different roles. For example, some additives can form a liquid phase at high temperature to promote sintering, thereby increasing the sintering density to increase the remanence; some additives can adhere to the grain boundary, inhibit the growth of grains, and thereby increase the existence rate of single-domain particles to improve the coercivity; some additives can also modify the grain boundary, make the grain surface smooth, reduce sharp corners, and improve squareness and orientation.
[0004] Rare earth elements have a unique 4f electron layer structure, high activity and large radius. They are widely used as additives to improve material properties, especially in the field of ceramic sintering, due to their own structural and chemical properties. However, in the production of sintered permanent magnet strontium ferrite, rare earth oxides are more often directly mixed with raw materials Fe2O3 and SrCO3 for sintering, so that rare earth ions enter the strontium ferrite lattice to replace Fe and Sr ions. For example, CN114195502A discloses a rare earth-doped permanent magnet ferrite and a preparation method thereof. The disclosed preparation method includes using ferric oxide, strontium carbonate, aluminum oxide, calcium carbonate, silicon dioxide, and nano-cerium oxide composites, mixing the above materials, adding water for wet ball milling, and after the ball milling is completed, pressing and molding to obtain a green body, which is sintered twice and cooled to obtain a rare earth-doped permanent magnet ferrite. However, few people add rare earth oxides as secondary additives to observe their effects on the magnetic properties of strontium ferrite. At the same time, in the production process of strontium ferrite, the secondary addition process usually adds conventional additives such as CaCO3, SiO2 and H3BO3 in sequence and mixes them with the strontium ferrite premix, which is usually not conducive to the uniform dispersion of the additives, thereby affecting the synergistic effect of the additives.
[0005] Among the magnetic properties of permanent strontium ferrite, remanence and coercivity are a pair of contradictory properties. The improvement of remanence benefits from the oriented growth of grains and the densification of the magnet during the sintering process. If the density is to be improved, it is inevitable to increase the sintering temperature moderately. However, the increase in sintering temperature will also cause excessive growth of grains, resulting in a gradual decrease in the proportion of single-domain particles, which in turn leads to a decrease in coercivity. Therefore, although the remanence can be slightly improved by simply continuing to increase the sintering temperature, it will be accompanied by a sharp decrease in coercivity. It is generally believed in the industry that when the remanence increases by 1Gs, the decrease in coercivity should be controlled at 3-5Oe, or the M value is used as the criterion for judging the comprehensive magnetic properties, where M=B r +H cJ / 3, the higher the M value, the higher the comprehensive magnetic properties of permanent magnet strontium ferrite.
[0006] Therefore, how to achieve uniform dispersion of additives during the secondary addition process, give full play to the role of each additive, and how to achieve an increase in the remanence of the permanent magnet strontium ferrite material while also increasing the coercive force accordingly or not significantly reducing it, thereby improving the overall magnetic properties of the permanent magnet strontium ferrite material, has become a problem that needs to be solved urgently. Summary of the invention
[0007] In order to solve the above technical problems, the present invention provides a permanent magnet strontium ferrite material and a preparation method and application thereof. The present invention first mixes rare earth oxides and additives to form a composite additive powder that is evenly mixed, has a small particle size and is uniform, directly avoiding the problem of uneven mixing of the components in the composite additive due to direct addition during the secondary addition process, and then mixes it with a strontium ferrite pre-sintered material. During the secondary addition process, the evenly mixed composite additive powder can be evenly distributed in the pre-sintered material, which is more conducive to the rare earth oxides in the composite additive and the additives to play a synergistic role, thereby improving the overall magnetic properties of the permanent magnet strontium ferrite material.
[0008] To achieve this object, the present invention adopts the following technical solutions:
[0009] In a first aspect, the present invention provides a method for preparing a permanent magnetic strontium ferrite material, the preparation method comprising the following steps:
[0010] (1) performing a first mixing of a rare earth oxide, an additive, and a first solvent to obtain a composite additive;
[0011] (2) The strontium ferrite pre-sintered material, the composite additive described in step (1) and the second solvent are mixed for a second time to obtain a mixed powder, which is pressed into shape to obtain a magnetic blank, which is sintered to obtain a permanent magnet strontium ferrite material.
[0012] In the present invention, the rare earth oxide and the additive are pre-mixed. First, the components can be mixed evenly. When the components are added for the second time, the synergistic effect of the components can be more easily exerted, thereby effectively improving the magnetic properties of the permanent magnet strontium ferrite material, avoiding the problem of uneven mixing of the components with the strontium ferrite pre-sintered material due to direct addition of the components. Second, the particle size of the composite additive can be made smaller and uniform, which is conducive to its attachment and movement on the grain boundary after mixing with the strontium ferrite pre-sintered material, and can inhibit the abnormal growth of grains, thereby improving the sintering efficiency. Third, the rare earth oxide is directly mixed with the conventional additive, which can further improve the reaction activity of the conventional additive, and is conducive to the orientation of the grains and the increase of the density of the magnet during the sintering process.
[0013] As a preferred technical solution of the present invention, the additives in step (1) include a calcium source, a silicon source, a boron source and a strontium source.
[0014] Preferably, the calcium source comprises C 12 H 22 O 14 Ca and inorganic calcium compounds.
[0015] Preferably, the inorganic calcium-containing compound includes any one of CaCO3, CaO or Ca(OH)2, or a combination of at least two of them.
[0016] Preferably, the silicon source comprises SiO2 or H2SiO3.
[0017] Preferably, the boron source includes any one of H3BO3, HBO2 or B2O3, or a combination of at least two of them.
[0018] Preferably, the strontium source includes any one of SrCO3, SrO or Sr(OH)2, or a combination of at least two of them.
[0019] Preferably, the rare earth oxide in step (1) includes La2O3 and / or CeO2.
[0020] In the present invention, rare earth oxides are mixed with conventional additives. Since rare earth elements have an unfilled 4f electron layer structure corresponding to a variety of electronic energy levels, they have many special and excellent physical and chemical properties, which can further improve the reaction activity of conventional additives, thereby facilitating the orientation of grains and the increase of magnet density during the sintering process.
[0021] Preferably, in the composite additive of step (1), the inorganic calcium-containing compound, C 12 H 22 O 14The mass ratio of Ca, silicon source, boron source, strontium source, La2O3 and CeO2 is (9-12):(3-6):(3-5):(1-2):(3-5):(0-4):(0-4), and not all of them are 0 at the same time, for example, 9:5:3:1:3:4:0, 9:5:3:1:3:0:4, 12:5:5:1:5:2:2 or 12:5:3:1:3:2:2, 12:5:3:1:4:2:2, etc., preferably (9-12):5:(3-5):1:(3-5):(0-4):(0-4), and not all of them are 0 at the same time.
[0022] As a preferred technical solution of the present invention, in step (1), the first solvent comprises deionized water.
[0023] Preferably, the mass ratio of the first solvent to the rare earth oxide and the additive as a whole is (5-9):1, such as 5:1, 6:1, 7:1, 8:1 or 9:1.
[0024] Preferably, the first mixing method in step (1) comprises ball milling.
[0025] In the present invention, the ball milling mixing method is adopted, and on the basis of uniform mixing, the particle size of the composite additive can be further refined, which is beneficial for the attachment and movement of the composite additive on the grain boundary, thereby improving the sintering efficiency.
[0026] Preferably, the ball milling time is 2 h-8 h, for example 2 h, 3 h, 4 h, 5 h, 6 h, 7 h or 8 h, etc., preferably 4 h-6 h.
[0027] Preferably, the rotation speed of the ball mill is 60 rpm-100 rpm, for example, 60 rpm, 70 rpm, 80 rpm, 90 rpm or 100 rpm.
[0028] Preferably, after the first mixing in step (1), step (1) further comprises the steps of dehydration, drying and grinding.
[0029] Preferably, the dehydration time is ≥12 h, such as 12 h, 15 h, 18 h, 20 h, 22 h, 25 h, 28 h or 30 h, etc., preferably 16 h-24 h.
[0030] Preferably, the drying temperature is 70°C-90°C, such as 70°C, 80°C or 90°C.
[0031] Preferably, the drying time is ≥12 h, such as 12 h, 15 h, 18 h, 20 h, 22 h, 25 h, 28 h or 30 h, etc., preferably 20 h-24 h.
[0032] As a preferred technical solution of the present invention, in step (2), the second solvent comprises deionized water.
[0033] Preferably, in step (2), the mass ratio of the strontium ferrite pre-sintered material, the composite additive and the second solvent is (80-120):(1-4):(100-300), for example, 100:1:100, 100:2:200, 100:3:300, 100:3:200, 100:4:200, 100:4:100, 100:3:100 or 100:4:300, etc., preferably 100:(2-3):(140-200).
[0034] Preferably, the second mixing method in step (2) comprises ball milling.
[0035] Preferably, the ball milling time is ≥12 h, for example, 12 h, 15 h, 18 h, 20 h, 22 h, 25 h, 28 h or 30 h.
[0036] Preferably, the rotation speed of the ball mill is 60 rpm-100 rpm, for example, 60 rpm, 70 rpm, 80 rpm, 90 rpm or 100 rpm.
[0037] Preferably, after the second mixing is completed, the average particle size of the powder in the mixed slurry is ≤1 μm, for example 0.99 μm, 0.95 μm, 0.90 μm, 0.85 μm, 0.80 μm, 0.75 μm, 0.70 μm, 0.65 μm, 0.60 μm or 0.50 μm, etc., preferably 0.85 μm-0.95 μm.
[0038] In the present invention, by adjusting the average particle size of the powder in the mixed slurry to ≤1 μm, the proportion of single-domain particles can be increased, thereby avoiding excessively large particle size, which leads to a decrease in coercive force and insignificant improvement in magnetic properties.
[0039] Preferably, after the second mixing in step (1), a dehydration step is further included to obtain a mixed powder.
[0040] Preferably, the dehydration time is ≥12 h, for example, 12 h, 15 h, 18 h, 20 h, 22 h, 25 h, 28 h or 30 h, etc.
[0041] Preferably, the solid content of the mixed powder is greater than 60%, such as 65%, 70%, 75% or 80%.
[0042] In the present invention, the solid content of the mixed powder is adjusted to be greater than 60%, so that the powder can be more easily pressed into shape.
[0043] As a preferred technical solution of the present invention, the pressure of the pressing molding is 300kg / cm 3 -600kg / cm 3, for example 300kg / cm 3 、350kg / cm 3 , 400kg / cm 3 , 450kg / cm 3 , 500kg / cm 3 、550kg / cm 3 or 600kg / cm 3 etc., preferably 400kg / cm 3 -500kg / cm 3 .
[0044] Preferably, an orientation magnetic field is also added during the compression molding process.
[0045] Preferably, the magnetizing current of the orientation magnetic field is 200A-400A, such as 200A, 250A, 300A, 350A or 400A, etc., preferably 250A-350A.
[0046] Preferably, the demagnetization current of the orientation magnetic field is 30A-60A, for example, 30A, 35A, 40A, 45A, 50A, 55A or 60A, etc., preferably 45A-55A.
[0047] In the present invention, the pressing pressure and the orientation magnetic field are used together to synergistically improve the orientation of the permanent magnet strontium ferrite material. The green body with better orientation will also have a higher orientation after sintering, which helps to improve the magnetic properties of strontium ferrite, especially to increase the remanence of strontium ferrite.
[0048] Preferably, after the compression molding, a drying step is also included.
[0049] As a preferred technical solution of the present invention, the sintering temperature is 1180℃-1230℃, for example, 1180℃, 1185℃, 1190℃, 1195℃, 1200℃, 1205℃, 1210℃, 1215℃, 1220℃, 1225℃ or 1230℃, etc.
[0050] In the present invention, the sintering temperature is adjusted to 1180°C-1230°C, which can increase the density of the permanent magnet strontium ferrite material and obtain a density of ≥4.9g / cm 3 The magnetic blank makes the permanent magnet strontium ferrite material have higher magnetic properties as a whole.
[0051] Preferably, the sintering holding time is 30 min-60 min, for example, 30 min, 35 min, 40 min, 45 min, 50 min, 55 min or 60 min.
[0052] Preferably, the heating rate of the sintering is 3°C / min-10°C / min, for example, 3°C / min, 4°C / min, 5°C / min, 6°C / min, 7°C / min, 8°C / min, 9°C / min or 10°C / min.
[0053] As a preferred technical solution of the present invention, the preparation method comprises the following steps:
[0054] (1) La2O3 and / or CeO2, C 12 H 22 O 14 Ca, an inorganic calcium-containing compound, a silicon source, a boron source, a strontium source and a first solvent are ball-milled at a speed of 60 rpm-100 rpm for 2 h-8 h to perform a first mixing, and then the mixed slurry after the first mixing is dehydrated for ≥12 h, dried at 70° C.-90° C. for ≥12 h and ground to obtain a composite additive;
[0055] In the composite additive, the inorganic calcium-containing compound, C 12 H 22 O 14 The mass ratios of Ca, silicon source, boron source, strontium source, La2O3 and CeO2 are (9-12):(3-6):(3-5):(1-2):(3-5):(0-4):(0-4), and are not 0 at the same time;
[0056] (2) The strontium ferrite pre-sintered material, the composite additive described in step (1) and the second solvent are ball-milled at a speed of 60 rpm-100 rpm for ≥12 h, and a second mixing is performed. The average particle size of the powder in the obtained mixed slurry is ≤1 μm. After dehydration for ≥12 h, a mixed powder with a solid content of >60% is obtained. The mixed powder is heated at 300 kg / cm 2 -600kg / cm 2 The magnetic blank is pressed and formed under a pressure of , and an oriented magnetic field is added during the pressing and forming process. The magnetizing current of the oriented magnetic field is 200A-400A, and the demagnetizing current is 30A-60A. After drying, a magnetic blank is obtained. The magnetic blank is heated to 1180℃-1230℃ at a heating rate of 3℃ / min-10℃ / min and sintered for 30min-60min to obtain a permanent magnetic strontium ferrite material;
[0057] The mass ratio of the strontium ferrite pre-sintered material, the composite additive and the second solvent is (80-120):(1-4):(100-300).
[0058] In a second aspect, the present invention further provides a permanent magnetic strontium ferrite material, which is prepared according to the preparation method described in the first aspect.
[0059] As a preferred technical solution of the present invention, the density of the permanent magnet strontium ferrite material is ≥4.9g / cm 3 , preferably 4.95 g / cm 3 -5.00g / cm 3 .
[0060] In a third aspect, the present invention further provides an application of the permanent magnetic strontium ferrite material according to the second aspect, or the permanent magnetic strontium ferrite material prepared according to the preparation method described in the first aspect, wherein the permanent magnetic strontium ferrite material is applied to the field of consumer electronics or the field of automotive electronics.
[0061] Compared with the prior art, the present invention has at least the following beneficial effects:
[0062] The invention introduces rare earth oxide as an additive into the production of a permanent magnet strontium ferrite material, and evenly mixes various additive components in advance to obtain a composite additive, and then mixes it with a strontium ferrite pre-sintered material. Compared with directly mixing the strontium ferrite pre-sintered material with various additive components, the permanent magnet strontium ferrite material obtained by the preparation method of the invention can maintain a remanence of 4050Gs-4099Gs and a coercive force of 3852Oe-4054Oe under the same raw materials and the same process conditions, and both the remanence and the coercive force can reach a relatively good standard at the same time, and the M value is in the range of 5383-5415, and the overall magnetic property is relatively good. BRIEF DESCRIPTION OF THE DRAWINGS
[0063] Figure 1 It is a schematic flow chart of the preparation method of Example 1 of the present invention.
[0064] Figure 2 This is a SEM picture of the mixed powder in Example 1 of the present invention after it is completely dried and sintered at 1220°C.
[0065] Figure 3 This is a SEM picture of the mixed powder in Example 2 of the present invention after it is completely dried and sintered at 1220°C.
[0066] Figure 4 This is a SEM picture of the mixed powder in Example 3 of the present invention after it is completely dried and sintered at 1220°C.
[0067] Figure 5 This is a SEM picture of the mixed powder in Example 7 of the present invention after it is completely dried and sintered at 1150°C.
[0068] Figure 6 This is a SEM picture of the mixed powder in Example 8 of the present invention after it is completely dried and sintered at 1250°C.
[0069] Figure 7This is a SEM picture of the mixed powder in Comparative Example 1 of the present invention after it is completely dried and sintered at 1220°C.
[0070] Figure 8 It is a schematic flow chart of the preparation method of Comparative Example 2 of the present invention.
[0071] Fig. 9 It is the XRD diagram of the permanent magnet strontium ferrite material prepared in Examples 1-3 and Comparative Examples 1-2 of the present invention. DETAILED DESCRIPTION
[0072] The technical solution of the present invention is further described below in conjunction with the accompanying drawings and through specific implementation methods. However, the following examples are only simplified examples of the present invention and do not represent or limit the scope of protection of the present invention. The scope of protection of the present invention shall be subject to the claims.
[0073] Unless otherwise specified, the raw materials and reagents used in the following examples are commercially available or can be prepared by known methods.
[0074] The chemical formula of the strontium ferrite pre-sintered material in the specific implementation mode of the present invention is SrFe 12 O 19 The preparation method of the strontium ferrite pre-sintered material comprises the following steps:
[0075] SrCO3 and Fe2O3 were weighed in a molar ratio of 1:6 and added to deionized water to cover the raw materials. The mixture was ball-milled at a speed of 80 rpm for 12 hours (the ball-to-material ratio was 10:1). After washing, the mixed powder was fully dried and heated to 1220°C at a heating rate of 5°C / min and sintered for 30 minutes. After crushing, strontium ferrite pre-sintered material was obtained.
[0076] Example 1
[0077] This embodiment provides a method for preparing a permanent magnet strontium ferrite material, the preparation method comprising the following steps:
[0078] (1) Weigh 45g CaCO3 and 25g C in a mass ratio of 9:5:5:1:5:2:2. 12 H 22 O 14 Ca, 25gSiO2, 5gH3BO3, 25gSrCO3, 10gLa2O3 and 10gCeO2, add 750g deionized water for ball milling (ball to material ratio is 10:1), ball milling for 4h at a frequency of 40Hz and a speed of 80rpm. After ball milling, pour it on a filter cloth, dehydrate for 18h, drain the water, dry it at 70℃ for 20h, and grind it evenly with an agate mortar to obtain a composite additive;
[0079] (2) Weigh 14.5 g of the composite additive, 500 g of strontium ferrite pre-sintered material and 850 g of deionized water for ball milling (ball to material ratio of 10:1), and ball milling for 14 h at a frequency of 40 Hz and a speed of 80 rpm. After the ball milling is completed, the mixed slurry is naturally air-dried for 18 h and dehydrated to obtain a mixed powder with a solid content of 63.7%. The mixed powder is oriented and formed using a hydraulic press at a forming pressure of 500 kg / cm 3 The magnetization current was 300A, the demagnetization current was 50A, and the magnet was dried at 70℃ for 4h to obtain a magnetic blank with a diameter of 26.5mm and a thickness of 13mm. The magnetic blank was heated to 1220℃ at a heating rate of 5℃ / min and sintered. The temperature was kept for 30min and the temperature was cooled with the furnace to obtain a density of 4.96g / cm 3 Permanent magnet strontium ferrite material.
[0080] Figure 1 The schematic diagram of the preparation method of Example 1 shows that CaCO3, C 12 H 22 O 14 The method comprises mixing Ca, SiO2, H3BO3, SrCO3, La2O3 and CeO2 uniformly to obtain a composite additive, and then mixing the composite additive with a strontium ferrite pre-sintered material.
[0081] Figure 2 The SEM image of the mixed powder in Example 1 after being completely dried and sintered at 1220° C. is shown. As can be seen from the image, most of the permanent magnet strontium ferrite grains have uniform size and rounded edges.
[0082] Example 2
[0083] This embodiment provides a method for preparing a permanent magnet strontium ferrite material. The difference between the preparation method and the embodiment 1 is that in step (1), 45g of CaCO3 and 25g of C 12 H 22 O 14 Ca, 25gSiO2, 5gH3BO3, 25gSrCO3 and 20gLa2O3, and the rest of the preparation method and parameters are consistent with Example 1.
[0084] Figure 3 The SEM image of the mixed powder in Example 2 after being completely dried and sintered at 1220° C. is shown. It can be seen from the image that the particle size of the permanent magnet strontium ferrite powder is all below 1 μm, and the size is uniform and appropriate.
[0085] Example 3
[0086] This embodiment provides a method for preparing a permanent magnet strontium ferrite material. The difference between the preparation method and the embodiment 1 is that in step (1), 45g of CaCO3 and 25g of C 12 H 22 O 14 Ca, 25gSiO2, 5gH3BO3, 25gSrCO3 and 20gCeO2, and the rest of the preparation method and parameters are consistent with Example 1.
[0087] Figure 4 The SEM image of the mixed powder in Example 3 after being completely dried and sintered at 1220° C. is shown. It can be seen from the image that many small particles are distributed on the larger particles. The presence of small particles will have a good effect on the coercive force of the permanent magnet strontium ferrite.
[0088] Example 4
[0089] This embodiment provides a method for preparing a permanent magnet strontium ferrite material, the preparation method comprising the following steps:
[0090] (1) Weigh 45g CaCO3 and 25g C in a mass ratio of 9:5:3:1:3:1:1. 12 H 22 O 14 Ca, 15gSiO2, 5gH3BO3, 15gSrCO3, 5gLa2O3 and 5gCeO2, add 690g deionized water for ball milling (ball to material ratio is 10:1), and ball mill for 2h at a frequency of 40Hz and a speed of 60rpm. After ball milling, pour it on the filter cloth, dehydrate for 16h, drain the water, dry it at 70℃ for 24h, and grind it evenly with an agate mortar to obtain a composite additive;
[0091] (2) Weigh 10g of the composite additive, 500g of strontium ferrite pre-sintered material and 700g of deionized water for ball milling (ball to material ratio of 10:1), and ball mill for 14h at a frequency of 40Hz and a speed of 60rpm. After ball milling, the mixed slurry was naturally air-dried for 18h and dehydrated to obtain a mixed powder with a solid content of 80%, which was oriented and formed using a hydraulic press at a forming pressure of 300kg / cm 3 The magnetization current was 200A, the demagnetization current was 30A, and the magnet was dried at 70℃ for 4h to obtain a magnetic blank with a diameter of 26.5mm and a thickness of 13mm. The magnetic blank was heated to 1180℃ at a heating rate of 3℃ / min and sintered. The temperature was kept for 60min and the temperature was cooled with the furnace to obtain a density of 4.95g / cm 3 Permanent magnet strontium ferrite material.
[0092] Example 5
[0093] This embodiment provides a method for preparing a permanent magnet strontium ferrite material, the preparation method comprising the following steps:
[0094] (1) Weigh 60g CaCO3 and 25g C in a mass ratio of 12:5:5:1:5:2:2. 12 H 22 O 14 Ca, 25gSiO2, 5gH3BO3, 25gSrCO3, 10gLa2O3 and 10gCeO2, add 1440g deionized water for ball milling (ball to material ratio is 10:1), and ball mill for 8h at a frequency of 40Hz and a speed of 100rpm. After ball milling, pour it on the filter cloth, dehydrate for 24h, drain the water, dry it at 70℃ for 22h, and grind it evenly with an agate mortar to obtain a composite additive;
[0095] (2) Weigh 15g of the composite additive, 500g of strontium ferrite pre-sintered material and 1000g of deionized water for ball milling (ball to material ratio of 10:1), and ball mill for 16h at a frequency of 40Hz and a speed of 100rpm. After ball milling, the mixed slurry was naturally air-dried for 20h and dehydrated to obtain a mixed powder with a solid content of 60%, which was oriented and formed using a hydraulic press at a forming pressure of 600kg / cm 3 The magnetization current is 400A, the demagnetization current is 60A, and the magnet is dried at 70℃ for 4h to obtain a magnet blank with a diameter of 26.5mm and a thickness of 13mm. The magnet blank is heated to 1230℃ at a heating rate of 10℃ / min and sintered. The temperature is kept for 45min and the temperature is cooled with the furnace to obtain a density of 5.00g / cm 3 Permanent magnet strontium ferrite material.
[0096] Example 6
[0097] This embodiment provides a method for preparing a permanent magnet strontium ferrite material. The difference between the preparation method and Example 1 is that in step (2), the ball milling time is 10 hours. After the ball milling is completed, the average particle size of the powder in the mixed slurry is 1.134 μm. The rest of the preparation method and parameters are consistent with Example 1.
[0098] Example 7
[0099] This embodiment provides a method for preparing a permanent magnet strontium ferrite material. The difference between the preparation method and embodiment 1 is that in step (2), the sintering temperature is 1150° C., and the rest of the preparation method and parameters are consistent with embodiment 1.
[0100] Figure 5 The SEM image of the mixed powder in Example 7 after being completely dried and sintered at 1150° C. is shown. It can be seen from the image that at the sintering temperature of 1150° C., the grain size is small and the edges and corners are sharp.
[0101] Example 8
[0102] This embodiment provides a method for preparing a permanent magnet strontium ferrite material. The difference between the preparation method and Example 1 is that in step (2), the sintering temperature is 1250° C., and the rest of the preparation method and parameters are consistent with Example 1.
[0103] Figure 6 The SEM image of the mixed powder in Example 8 after being completely dried and sintered at 1250° C. is shown. It can be seen from the image that the grains are tightly fused together, connected into one piece, are larger in size and are denser as a whole.
[0104] Example 9
[0105] This embodiment provides a method for preparing a permanent magnet strontium ferrite material. The difference between the preparation method and embodiment 1 is that in step (2), the pressing pressure is 280 kg / cm 3 The rest of the preparation methods and parameters were the same as those in Example 1.
[0106] Example 10
[0107] This embodiment provides a method for preparing a permanent magnet strontium ferrite material. The difference between the preparation method and the embodiment 1 is that in step (2), the pressing pressure is 620 kg / cm 3 The rest of the preparation methods and parameters were the same as those in Example 1.
[0108] Comparative Example 1
[0109] This comparative example provides a method for preparing a permanent magnet strontium ferrite material. The difference between the preparation method and Example 1 is that in step (1), La2O3 and CeO2 are omitted, and 45g CaCO3, 25g CeO2 and 10g CaCO3 are weighed according to a mass ratio of 9:5:5:1:5:0:0. 12 H 22 O 14 Ca, 25 g SiO2, 5 g H3BO3 and 25 g SrCO3, and the rest of the preparation method and parameters are consistent with Example 1.
[0110] Figure 7 The SEM image of the mixed powder in Comparative Example 1 after being completely dried and sintered at 1220° C. is shown. It can be seen from the image that there are many large particles with a size of about 2 μm, which will cause the coercive force of the magnet to deteriorate.
[0111] Comparative Example 2
[0112] This comparative example provides a method for preparing a permanent magnet strontium ferrite material. The difference between the preparation method and Example 1 is that step (1) is omitted. In step (2), 4.5 g of CaCO3 and 2.5 g of C 12 H 22 O 14 Ca, 2.5 g SiO2, 0.5 g H3BO3, 2.5 g SrCO3, 1 g La2O3, 1 g CeO2, 500 g strontium ferrite pre-sintered material and 850 g water were ball-milled, and the rest of the preparation method and parameters were consistent with those in Example 1.
[0113] Figure 8 The schematic diagram of the preparation method of Comparative Example 2 shows that the method directly uses CaCO3 and C 12 H 22 O 14 A method for uniformly mixing Ca, SiO2, H3BO3, SrCO3, La2O3, CeO2 and strontium ferrite pre-sintered materials.
[0114] The permanent magnet strontium ferrite materials prepared in Examples 1-10 and Comparative Examples 1-2 were measured for coercive force H using a BH instrument. cJ and remanence B r , and calculate the M value, M = B r +H cJ / 3; using a particle size analyzer to test the average particle size of the powder in the mixed slurry obtained after the second mixing in Example 1-10 and Comparative Example 1-2; testing the XRD pattern of the permanent magnetic strontium ferrite material prepared in Example 1-10 and Comparative Example 1-2, and then using the texture factor formula The respective orientation degrees are calculated and the specific data are shown in Table 1.
[0115] Fig. 9 The XRD patterns of the permanent magnetic strontium ferrite materials prepared in Examples 1-3 and Comparative Examples 1-2 are shown. It can be seen from the figure that the diffraction peak intensities corresponding to the crystal planes (004), (006), (008) and (0014) are relatively high, indicating that the strontium ferrite has obvious preferential orientation along the C-axis during the pressing and sintering processes. The higher the degree of preferential orientation of the grains along the C-axis, the better the macroscopic magnetic properties such as remanence and coercive force will be.
[0116] Table 1
[0117] project <![CDATA[Residual magnetism B r (Gs)]]> <![CDATA[Coercive force H cJ (Oe)]]> M-value Orientation Average particle size (μm) Example 1 4061 4022 5402 0.612 0.891 Example 2 4060 3992 5391 0.593 0.896 Example 3 4081 4003 5415 0.609 0.880 Example 4 4050 4054 5401 0.540 0.843 Example 5 4099 3852 5383 0.604 0.821 Example 6 4073 3821 5347 0.527 1.134 Example 7 4043 4007 5379 0.518 0.876 Example 8 4115 3650 5332 0.626 0.882 Example 9 4045 3980 5372 0.670 0.889 Example 10 4028 3930 5338 0.501 0.885 Comparative Example 1 4032 3890 5329 0.587 0.893 Comparative Example 2 4015 3894 5313 0.581 0.902
[0118] The test results show that:
[0119] (1) It can be seen from Examples 1 to 5 that the present invention can improve the magnetic properties of permanent magnet strontium ferrite materials by first mixing rare earth oxides and additives to form a uniformly mixed composite additive powder, and then mixing the composite additive powder with strontium ferrite pre-sintered material, and the coercive force does not decrease while the remanence is increased. Specifically, the remanence can be maintained at 4050Gs-4099Gs, and the coercive force can be maintained at 3852Oe-4054Oe. Both the remanence and the coercive force can reach better standards at the same time, the M value is in the range of 5383-5415, and the overall magnetic properties are better.
[0120] (2) It can be seen from Examples 1 and 6 that the present invention can further improve the coercive force by further regulating the ball milling time and regulating the average particle size of the powder in the mixed slurry obtained after the second mixing to be ≤1 μm, thereby avoiding the reduction of initial single-domain particles due to excessively large particle size, which makes the improvement of coercive force not obvious.
[0121] (3) It can be seen from Example 1 and Example 7 to Example 8 that the present invention can make the permanent magnet strontium ferrite material have a higher density by further adjusting the sintering temperature at 1180°C-1230°C, so that the magnet exhibits better magnetic properties, and prevents the magnet from having a low remanence and a high coercive force due to insufficient density, or the magnet from being over-burned and causing the particle size to increase, so that although a larger remanence can be obtained, the coercive force drops sharply.
[0122] (4) It can be seen from Examples 1 and 9 to 10 that the present invention further adjusts the pressing pressure to 300 kg / cm 2 -600kg / cm 2 , combined with the oriented magnetic field, the permanent magnet strontium ferrite material can have a higher degree of orientation, thereby improving the remanence. Although too low a pressing pressure is more conducive to green body orientation, it will cause the green body density to decrease and affect the remanence. Too high a pressing pressure will lead to poor green body orientation and affect the improvement of orientation during the sintering process.
[0123] (5) It can be seen from Example 1 and Comparative Example 1 that the present invention can improve the orientation degree of strontium ferrite, promote the mass transfer efficiency during the sintering process, and inhibit the excessive growth of grains to a certain extent by adding rare earth oxides to the composite additive, thereby improving the magnetic properties of the permanent magnetic strontium ferrite material. After adding rare earth oxides, it does not affect the particle size of the mixed slurry, which indirectly verifies that it works at the grain boundary during the subsequent sintering process; when rare earth oxides are not added, it cannot achieve the effect of inhibiting the excessive growth of grains, thereby causing the magnetic properties of the permanent magnetic strontium ferrite material to decrease;
[0124] In addition, while the remanence is improved, the coercive force is also improved to a certain extent, thereby taking into account the remanence and coercive force of the permanent magnet strontium ferrite material, making the overall magnetic properties better.
[0125] (6) It can be seen from Example 1 and Comparative Example 2 that the present invention first forms a composite additive powder with uniform mixing, small particle size and uniformity by first mixing the rare earth oxide with the additive. On the one hand, the mass transfer rate during the sintering process is improved, so that the magnet is sintered more fully. On the other hand, the small particles adhere to the grain boundaries of the strontium ferrite, play a pinning role, and inhibit the abnormal growth of the grains. In addition, it can be seen from the XRD spectrum and texture factor that the addition of the composite additive promotes the preferential orientation of the particles along the C axis. The SEM micromorphology also shows that in Example 1, the grain agglomeration is reduced, the dispersion is better, and the particle size is more uniform. Taking all aspects into consideration, the comprehensive magnetic properties of the strontium ferrite are improved.
[0126] However, when all additives are directly added into the strontium ferrite pre-sintered material, the synergistic effect between the additives is difficult to exert, and it is easy to cause uneven growth of grains, and the modification effect cannot be better demonstrated.
[0127] In summary, the present invention first mixes the rare earth oxide and the additive to form a composite additive powder that is evenly mixed, has a small particle size and is uniform, directly avoiding the problem of uneven mixing of the components in the composite additive during the secondary addition process due to direct addition, and then mixes it with the strontium ferrite pre-sintered material. During the secondary addition process, the evenly mixed composite additive powder can be evenly distributed in the pre-sintered material, which is more conducive to the rare earth oxide in the composite additive and the additives to play a synergistic role, thereby improving the magnetic properties of the permanent magnet strontium ferrite material.
[0128] The applicant declares that the above is only a specific implementation mode of the present invention, but the protection scope of the present invention is not limited thereto. Those skilled in the art should understand that any changes or substitutions that can be easily thought of by those skilled in the art within the technical scope disclosed by the present invention shall fall within the protection scope and disclosure scope of the present invention.
Claims
1. A method for preparing a permanent magnet strontium ferrite material, characterized in that: The preparation method comprises the following steps: (1) performing a first mixing of a rare earth oxide, an additive, and a first solvent to obtain a composite additive; (2) The strontium ferrite pre-sintered material, the composite additive described in step (1) and the second solvent are mixed for a second time to obtain a mixed powder, which is pressed into shape to obtain a magnetic blank, which is sintered to obtain a permanent magnet strontium ferrite material.
2. The preparation method according to claim 1, characterized in that: The additives in step (1) include a calcium source, a silicon source, a boron source and a strontium source; Preferably, the calcium source comprises C 12 H 22 O 14 Ca and inorganic calcium compounds; Preferably, the inorganic calcium-containing compound comprises any one or a combination of at least two of CaCO3, CaO or Ca(OH)2; Preferably, the silicon source comprises SiO2 or H2SiO3; Preferably, the boron source comprises any one or a combination of at least two of H3BO3, HBO2 or B2O3; Preferably, the strontium source comprises any one of SrCO3, SrO or Sr(OH)2 or a combination of at least two thereof; Preferably, the rare earth oxide in step (1) comprises La2O3 and / or CeO2; Preferably, in the composite additive of step (1), the inorganic calcium-containing compound, C 12 H 22 O 14 The mass ratio of Ca, silicon source, boron source, strontium source, La2O3 and CeO2 is (9-12):(3-6):(3-5):(1-2):(3-5):(0-4):(0-4), and not all of them are 0 at the same time, preferably (9-12):5:(3-5):1:(3-5):(0-4):(0-4), and not all of them are 0 at the same time.
3. The preparation method according to claim 1 or 2, characterized in that: Step (1) the first solvent comprises deionized water; Preferably, the mass ratio of the first solvent to the rare earth oxide and the additive as a whole is (5-9):1; Preferably, the first mixing method in step (1) comprises ball milling; Preferably, the ball milling time is 2h-8h, preferably 4h-6h; Preferably, the rotation speed of the ball mill is 60rpm-100rpm; Preferably, after the first mixing in step (1), step (1) further comprises the steps of dehydration, drying and grinding; Preferably, the dehydration time is ≥ 12 h, preferably 16 h to 24 h; Preferably, the drying time is ≥12 h, preferably 20 h-24 h.
4. The preparation method according to any one of claims 1 to 3, characterized in that Step (2) the second solvent comprises deionized water; Preferably, in step (2), the mass ratio of the strontium ferrite pre-sintered material, the composite additive and the second solvent is (80-120):(1-4):(100-300), preferably 100:(2-3):(140-200); Preferably, the second mixing method in step (2) comprises ball milling; Preferably, the ball milling time is ≥12h; Preferably, the rotation speed of the ball mill is 60rpm-100rpm; Preferably, after the second mixing is completed, the average particle size of the powder in the mixed slurry is ≤1 μm, preferably 0.85 μm-0.95 μm; Preferably, after the second mixing in step (1), step (1) further comprises a dehydration step to obtain a mixed powder; Preferably, the dehydration time is ≥ 12 h; Preferably, the solid content of the mixed powder is greater than 60%.
5. The preparation method according to any one of claims 1 to 4, characterized in that: The compression molding pressure is 300 kg / cm 2 -600kg / cm 2 , preferably 400kg / cm 2 -500kg / cm 2 ; Preferably, during the pressing process, an orientation magnetic field is also added; Preferably, the magnetizing current of the orientation magnetic field is 200A-400A, preferably 250A-350A; Preferably, the demagnetization current of the orientation magnetic field is 30A-60A, preferably 45A-55A; Preferably, after the compression molding, a drying step is also included.
6. The preparation method according to any one of claims 1 to 5, characterized in that: The sintering temperature is 1180°C-1230°C; Preferably, the sintering holding time is 30min-60min; Preferably, the heating rate of the sintering is 3°C / min-10°C / min.
7. The preparation method according to claim 1, characterized in that: The preparation method comprises the following steps: (1) La2O3 and / or CeO2, C 12 H 22 O 14 Ca, an inorganic calcium-containing compound, a silicon source, a boron source, a strontium source and a first solvent are ball-milled at a speed of 60 rpm-100 rpm for 2 h-8 h to perform a first mixing, and then the mixed slurry after the first mixing is dehydrated for ≥12 h, dried at 70° C.-90° C. for ≥12 h and ground to obtain a composite additive; In the composite additive, the inorganic calcium-containing compound, C 12 H 22 O 14 The mass ratios of Ca, silicon source, boron source, strontium source, La2O3 and CeO2 are (9-12):(3-6):(3-5):(1-2):(3-5):(0-4):(0-4), and are not 0 at the same time; (2) The strontium ferrite pre-sintered material, the composite additive described in step (1) and the second solvent are ball-milled at a speed of 60 rpm-100 rpm for ≥12 h, and a second mixing is performed. The average particle size of the powder in the obtained mixed slurry is ≤1 μm. After dehydration for ≥12 h, a mixed powder with a solid content of >60% is obtained. The mixed powder is heated at 300 kg / cm 2 -600kg / cm 2 The magnetic blank is pressed and formed under a pressure of , and an oriented magnetic field is added during the pressing and forming process. The magnetizing current of the oriented magnetic field is 200A-400A, and the demagnetizing current is 30A-60A. After drying, a magnetic blank is obtained. The magnetic blank is heated to 1180℃-1230℃ at a heating rate of 3℃ / min-10℃ / min and sintered for 30min-60min to obtain a permanent magnetic strontium ferrite material; The mass ratio of the strontium ferrite pre-sintered material, the composite additive and the second solvent is (80-120):(1-4):(100-300).
8. A permanent magnet strontium ferrite material, characterized in that: The permanent magnet strontium ferrite material is prepared according to the preparation method according to any one of claims 1-7.
9. The permanent magnet strontium ferrite material according to claim 8, characterized in that: The density of the permanent magnet strontium ferrite material is ≥4.9g / cm 3 , preferably 4.95 g / cm 3 -5.00g / cm 3 .
10. A permanent magnetic strontium ferrite material according to claim 8 or 9, or a use of the permanent magnetic strontium ferrite material prepared according to the preparation method according to any one of claims 1 to 7, characterized in that: The permanent magnet strontium ferrite material is applied in the field of consumer electronics or automotive electronics.
Citation Information
Patent Citations
Rare earth doped permanent magnetic ferrite and preparation method thereof
CN114195502A
Preparation method for rare earth permanent ferrite magnetic shoe and product
CN101860091A
Rare earth-containing permanent magnetic ferrite and manufacturing method thereof
CN104496457A
JP1975041092A
Permanent magnet and method for preparation thereof
US20040028946A1